Layer‐by‐layer bioassembly of poly(lactic) acid membranes loaded with coculture of HBMSCs and EPCs improves vascularization in vivo. Issue 12 (22nd August 2019) - Guduric, Vera; Siadous, Robin; Babilotte, Joanna; Seimbille, Maxime; Bareille, Reine; Rey, Sylvie; Thébaud, Noëlie B.; Le Nihouannen, Damien; Fricain, Jean‐Christophe; Devillard, Raphaël; Luzanin, Ognjan; Catros, Sylvain
Abstract: Layer‐by‐layer (LBL) BioAssembly method was developed to enhance the control of cell distribution within 3D scaffolds for tissue engineering applications. The objective of this study was to evaluate in vivo the development of blood vessels within LBL bioassembled membranes seeded with human primary cells, and to compare it to cellularized massive scaffolds. Poly(lactic) acid (PLA) membranes fabricated by fused deposition modeling were seeded with monocultures of human bone marrow stromal cells or with cocultures of these cells and endothelial progenitor cells. Then, four cellularized membranes were assembled in LBL constructs. Early osteoblastic and endothelial cell differentiation markers, alkaline phosphatase, and von Willebrand's factor, were expressed in all layers of assemblies in homogenous manner. The same kind of LBL assemblies as well as cellularized massive scaffolds was implanted subcutaneously in mice. Human cells were observed in all scaffolds seeded with cells, but not in the inner parts of massive scaffolds. There were significantly more blood vessels observed in LBL bioassemblies seeded with cocultures compared to all other samples. LBL bioassembly of PLA membranes seeded with a coculture of human cells is an efficient method to obtain homogenous cell distribution and blood vessel formation within the entire volume of a 3D composite scaffold.